Edukasi dan Suplementasi Tablet Fe Meningkatkan Kadar Hemoglobin Ibu Hamil Anemia - Satriani Satriani; Ratnawati Ratnawati (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2022)
Anemia in pregnant women is a health problem that occurs during pregnancy. Anemia due to iron deficiency in pregnancy has an impact on the risk of a mother having a miscarriage, low birth weight babies (LBW), bleeding during childbirth and can cause death for the mother and baby. This study aims to determine educational interventions and Fe tablet supplementation on hemoglobin levels of anemic pregnant women in the working areas of the Trauma Center Health Center, Harapan Baru Health Center, and Mangkupalas Health Center, Samarinda City. The design used in this study was a quasi-experimental study with a pretest posttest with a control group. The sample consisted of 17 people divided into 9 people in the intervention group and 8 people in the control group. The intervention group received education using the counseling method using flipchart media and Fe tablet supplementation, while the control group received education without the counseling method using leaflet media and Fe tablet supplementation for 30 days. Data analysis used paired t test and independent t test. The results showed that most of the respondents in the intervention group before education had good knowledge criteria, namely 8 people (88.9%), while after education had good knowledge criteria, namely 9 people (100%). Most of the respondents in the intervention group after counseling experienced an increase in Hb > 1g/dl as many as 5 people. There was no significant difference in the increase in Hb levels in the intervention and control groups after the educational intervention and Fe tablet supplementation (p=0.077). Keywords: Anemia of Pregnant Women, Education, Fe Tablet Supplementation